Importance of Validating Antibodies and Small Compound Inhibitors Using Genetic Knockout Studies—T Cell Receptor-Induced CYLD Phosphorylation by IKKε/TBK1 as a Case Study - Lork, Marie; Kreike, Marja; Staal, Jens; Beyaert, Rudi (Frontiers in Cell and Developmental Biology, 2018)
CYLD is a deubiquitinating enzyme that plays a crucial role in immunity and inflammation as a negative regulator of NF-κB transcription factor and JNK kinase signaling. Defects in either of these pathways contribute to the progression of numerous inflammatory and autoimmune disorders. Therefore we set out to unravel molecular mechanisms that control CYLD activity in the context of T cell receptor (TCR) signaling. More specifically, we focused on CYLD phosphorylation at Ser418, which can be detected upon immunoblotting of cell extracts with phospho(Ser418)-CYLD specific antibodies. Jurkat T cells stimulated with either anti-CD3/anti-CD28 or PMA/Ionomycin (to mimic TCR signaling) were used as a model system. The role of specific kinases was analyzed using pharmacological as well as genetic approaches. Our initial data indicated that CYLD is directly phosphorylated by the noncanonical IκB kinases (IKKs) IKKε and TANK Binding Kinase 1 (TBK1) at Ser418 upon TCR stimulation. Treatment with MRT67307, a small compound inhibitor for IKKε and TBK1, inhibited TCR-induced CYLD phosphorylation. However, the phospho(Ser418)-CYLD antibodyimmunoreactive band was still present in CRISPR/Cas9 generated IKKε/TBK1 double knockout cell lines, where it could still be prevented by MRT67307, indicating that the initially observed inhibitory effect of MRT67307 on TCR-induced CYLD phosphorylation is IKKε/TBK1-independent. Most surprisingly, the phospho(Ser418)-CYLD immunoreactive band was still detectable upon immunoblotting of cell extracts obtained from CYLD deficient cells. These data demonstrate the non-specificity of MRT67307 and phospho(Ser418)-CYLD specific antibodies, implicating that previously published results based on these tools may also have led to wrong conclusions. We therefore advise to use genetic knockout studies or alternative approaches for a better validation of antibodies and small compound inhibitors. Interestingly, immunoprecipitation with the phospho(Ser418)-CYLD antibody, followed by immunoblotting with anti-CYLD, revealed that CYLD is phosphorylated by IKKε/TBK1 at Ser418 upon T cell stimulation, but that its direct detection with the phospho(Ser418)-CYLD-specific antibody in a western blot is masked by another inducible protein of the same size that is recognized by the same antibody.